Inflammatory models of cutaneous hyperalgesia are sensitive to effects of ibuprofen in man - Kilo, S; Forster, C; Geisslinger, G; Brune, K; Handwerker, H O (Pain (Amsterdam), 1995)
A new experimental procedure was developed to quantify the analgesic actions of non-steroidal anti-inflammatory drugs (NSAIDs) in healthy human subjects. In order to mimic the clinical situation, the drug was 'therapeutically' administered 1 day after induction of inflammation by freezing a small skin area. The procedure was easily tolerated and led to a marked hyperalgesia without ongoing pain which was tested using mechanical impact stimulation and magnitude estimation. For comparison, we used a previously established model of repeated noxious pinching of an interdigital skin web which induces a hyperalgesia to pressure (rated via visual analogue scale), and topical application of capsaicin which leads to quantifiable flare and allodynia responses. The effects of a cumulative drug regime of ibuprofen in 2 different doses (3 x 400 mg and 3 x 800 mg at 2-h intervals) were tested versus placebo using a double-blind cross-over design with 24 volunteers of either gender. Ibuprofen caused a significant suppression of the hyperalgesia to repeated pinching and of the hyperalgesia to impact stimulation following freeze trauma. In contrast, there was no effect on the areas of flare and allodynia induced by capsaicin application and on the impact evoked sensations from untreated skin. The two dosages of ibuprofen, however, appeared to be equally effective in a way that suggests a plateauing of the antihyperalgesic effect. The two models in which hyperalgesia is affected by ibuprofen, i.e., repeated pinching and impact stimulation after freeze trauma, seem to provide comparable sensitivity. The freeze model may in the future have the advantage to allow for a better temporal resolution of the drug's action profile.